Обыкновенные ребята: рассказы / Лев Кассиль - Кассиль Лев Абрамович (Логосвос, 2017)
Экземпляры: БС (20171101) / Инвентарный номер: РТШ54642 / Цена: / Сис.шифр: Р2 / Авт.знак: К 28 / ГРНТИ: 17.82.32 / ББК: 84(2)